Água subterrânea na bacia experimental de Aiuaba-CE - Silva, José Edberto da (2008)
Experimental Hydrografic Basin of Aiuaba (BEA) is located inside of the Aiuaba Ecological Station, in Aiuaba city, State of Ceará, therefore, without antropic action (fertilizing, pollution sources, impacts, etc). The underground flow in porous and fractured medium is unknown in the region. For its study, a geophysical study was executed using the “Very Low Frequency” (VLF) method to identify the types of existing rocks fractures in the region, as well to allow to visualization of its depths and extensions. This study was also used to locate the wells in the region to show the geologic characteristics of the rocks. Some wells had been perforateed by the Superintendência de Obras Hidráulicas (SOHIDRA), with the technician support of the Companhia de Recursos Minerais – Serviços Geológicos do Brasil (CPRM). The water of these wells, most of the time, presents high salinity, with exception of some of them, situated in the Gameleira Basin in neighborhoods of BEA. The saline water is used for irrigation and animals consumption, whereas good quality water is for the human consumption. For the calculation of BEA water balance was made a multicriteria analysis of the fractured aquifer behavior. The direction and course of underground flow had been determined from data of the wells, associated to the topographical studies, in the same local, of the VLF profiles. The soil overlapping to the rocks has similar characteristics to the material that fills the fractures, It was made some tests, such as: petrografic in the rock, permeability and granulometric in the soil and physicist-chemistries in wells water of the region, proving the raised hypotheses. The value of the aquifers hydraulic conductivity, on average, is approximately 1.61 x 10-2 m/h.